2021
DOI: 10.1111/bcpt.13692
|View full text |Cite
|
Sign up to set email alerts
|

High anticholinergic burden at admission associated with in‐hospital mortality in older patients: A comparison of 19 different anticholinergic burden scales

Abstract: Although no gold standard exists to assess a patient's anticholinergic burden, a review identified 19 anticholinergic burden scales (ABSs). No study has yet evaluated whether a high anticholinergic burden measured with all 19 ABSs is associated with in‐hospital mortality and length of stay (LOS). We conducted a cohort study at a Swiss tertiary teaching hospital using patients' electronic health record data from 2015–2018. Included were patients aged ≥65 years, hospitalised ≥48 h without stays and >24 h in inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 60 publications
2
14
1
Order By: Relevance
“…We replicated the lack of association between cognitive impairment in bipolar patients and Anticholinergic Drug Scale values reported by Eum et al (2017). Previous use of Chew's scale showed its association with cognitive impairment in elderly patients (Lampela et al, 2013;Lisibach et al, 2021), whereas the Anticholinergic Toxicity Scale has been shown to be strongly associated with delirium and mortality in elderly patients (Lisibach et al, 2022a(Lisibach et al, & 2022b, but no study has explored their association with cognitive performance for individuals with psychiatric disorders. Indeed, Chew's scale was designed based exclusively on in vitro measures of serum anticholinergic activity and the Anticholinergic Toxicity Scale was designed based on the affinity for muscarinic receptors deduced from the molecular structure of the drug: neither of the two scales were designed based on clinical observations, making our results quite unexpected.…”
Section: Discussionsupporting
confidence: 72%
“…We replicated the lack of association between cognitive impairment in bipolar patients and Anticholinergic Drug Scale values reported by Eum et al (2017). Previous use of Chew's scale showed its association with cognitive impairment in elderly patients (Lampela et al, 2013;Lisibach et al, 2021), whereas the Anticholinergic Toxicity Scale has been shown to be strongly associated with delirium and mortality in elderly patients (Lisibach et al, 2022a(Lisibach et al, & 2022b, but no study has explored their association with cognitive performance for individuals with psychiatric disorders. Indeed, Chew's scale was designed based exclusively on in vitro measures of serum anticholinergic activity and the Anticholinergic Toxicity Scale was designed based on the affinity for muscarinic receptors deduced from the molecular structure of the drug: neither of the two scales were designed based on clinical observations, making our results quite unexpected.…”
Section: Discussionsupporting
confidence: 72%
“…This study was approved by the Swiss ethics review committee (EKNZ Project ID: 2018–01000). A similar study investigating the association of the ACH burden with in‐hospital mortality and length of stay was published using the same data set 29 …”
Section: Methodsmentioning
confidence: 99%
“…A similar study investigating the association of the ACH burden with in‐hospital mortality and length of stay was published using the same data set. 29 …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations